A novel de novo Myocilin variant in a patient with sporadic juvenile open angle glaucoma. Issue 1 (December 2016) - Souzeau, Emmanuelle; Burdon, Kathryn; Ridge, Bronwyn; Dubowsky, Andrew; Ruddle, Jonathan; Craig, Jamie
Abstract Background Glaucoma is a leading cause of irreversible blindness. Pathogenic variants in theMyocilin gene (MYOC ) cause juvenile open angle glaucoma (JOAG) in 8–36 % of cases, and display an autosomal dominant inheritance with high penetrance. Molecular diagnosis is important for early identification as therapies are effective in minimizing vision loss andMYOC variants can be associated to severe glaucoma.MYOC variants are usually inherited, however a fifth of carriers do not report a family history. The occurrence ofde novo MYOC variants is currently unknown. Case presentation In this study we investigated a 14 year old male Caucasian patient diagnosed with JOAG, and no family history of glaucoma. A novel probably deleterious MYOC:p.(Pro254Leu) variant was identified in the index case. This variant was not present in the parents or the siblings. Conclusion This is the second report of ade novo MYOC variant in a sporadic case of JOAG and it is currently unknown if this mechanism occurs more frequently. This finding emphasizes the importance of screening individuals with JOAG forMYOC mutations irrespective of a negative family history.